Why Do Pregnant Women Die? A Review of Maternal Deaths From 1990 to 2010 at the University of Alabama at Birmingham. Issue 3 (September 2015) - Frölich, M.A.; Banks, C.; Brooks, A.; Sellers, A.; Swain, R.; Cooper, L.
<x xml:space="preserve">Abstract</x> (Anesth Analg. 2014;119(5):1135–1139)